Developmental Toxicity of Zinc Oxide Nanoparticles to Zebrafish (Danio rerio): A Transcriptomic Analysis. - Jin Soo Choi; Ryeo-Ok Kim; Seokjoo Yoon; Woo-Keun Kim (PLoS ONE, 2016)
Zinc oxide nanoparticles (ZnO NPs) are being utilized in an increasing number of fields and commercial applications. While their general toxicity and associated oxidative stress have been extensively studied, the toxicological pathways that they induce in developmental stages are still largely unknown. In this study, the developmental toxicity of ZnO NPs to embryonic/larval zebrafish was investigated. The transcriptional expression profiles induced by ZnO NPs were also investigated to ascertain novel genomic responses related to their specific toxicity pathway. Zebrafish embryos were exposed to 0.01, 0.1, 1, and 10 mg/L ZnO NPs for 96 h post-fertilization. The toxicity of ZnO NPs, based on their Zn concentration, was quite similar to that in embryonic/larval zebrafish exposed to corresponding ZnSO4 concentrations. Pericardial edema and yolk-sac edema were the principal malformations induced by ZnO NPs. Gene-expression profiling using microarrays demonstrated 689 genes that were differentially regulated (fold change >1.5) following exposure to ZnO NPs (498 upregulated, 191 downregulated). Several genes that were differentially regulated following ZnO NP exposure shared similar biological pathways with those observed with ZnSO4 exposure, but six genes (aicda, cyb5d1, edar, intl2, ogfrl2 and tnfsf13b) associated with inflammation and the immune system responded specifically to ZnO NPs (either in the opposite direction or were unchanged in ZnSO4 exposure). Real-time reverse-transcription quantitative polymerase chain reaction confirmed that the responses of these genes to ZnO NPs were significantly different from their response to ZnSO4 exposure. ZnO NPs may affect genes related to inflammation and the immune system, resulting in yolk-sac edema and pericardia edema in embryonic/larval developmental stages. These results will assist in elucidating the mechanisms of toxicity of ZnO NPs during development of zebrafish.